Non-hematopoietic PAR-2 is essential for matriptase-driven pre-malignant progression and potentiation of ras-mediated squamous cell carcinogenesis - Sales, K. U.; Friis, S.; Konkel, J. E.; Godiksen, S.; Hatakeyama, M. [UNESP]; Hansen, K. K.; Rogatto, S. R. [UNESP]; Szabo, R.; Vogel, L. K.; Chen, W.; Gutkind, J. S.; Bugge, T. H. (Nature Publishing Group, 2015)
The membrane-anchored serine protease, matriptase, is consistently dysregulated in a range of human carcinomas, and high matriptase activity correlates with poor prognosis. Furthermore, matriptase is unique among tumor-associated proteases in that epithelial stem cell expression of the protease suffices to induce malignant transformation. Here, we use genetic epistasis analysis to identify proteinase-activated receptor (PAR)-2-dependent inflammatory signaling as an essential component of matriptase-mediated oncogenesis. In cell-based assays, matriptase was a potent activator of PAR-2, and PAR-2 activation by matriptase caused robust induction of nuclear factor (NF)kappa B through G alpha i. Importantly, genetic elimination of PAR-2 from mice completely prevented matriptase-induced pre-malignant progression, including inflammatory cytokine production, inflammatory cell recruitment, epidermal hyperplasia and dermal fibrosis. Selective ablation of PAR-2 from bone marrow-derived cells did not prevent matriptase-driven pre-malignant progression, indicating that matriptase activates keratinocyte stem cell PAR-2 to elicit its pro-inflammatory and pro-tumorigenic effects. When combined with previous studies, our data suggest that dual induction of PAR-2-NF kappa B inflammatory signaling and PI3K-Akt-mTor survival/proliferative signaling underlies the transforming potential of matriptase and may contribute to pro-tumorigenic signaling in human epithelial carcinogenesis.
Keywords: Epithelial carcinogenesis; Inflammation; Keratinocyte stem cells; Pericellular proteolysis